Auditoría de gestión a los procesos administrativos del cuerpo de Bomberos municipal del cantón La Mana, periodo 2017 - Ayala Páez, Gladys Mariela (2019)
The present investigation was carried out in the Fire Department of the Canton La Maná, whose mission is to provide the community with integral emergency call services in the prevention and extinction of fires, rescue of people and animals, assistance in civic disasters, floods, traffic accidents, among others. Its objective is focused on evaluating the incidence of the management audit in the management of administrative processes, 2017 period, based on the question: How does management audit affect the administrative processes of the Municipal Fire Department of La Maná cantón?. It is important to state that there is inadequate administrative management in the institution, which negatively affects the results reflected by the inadequate use of material and human resources. Based on the exposed problems, an analysis of the current situation of the administrative management was made; the degree of efficiency, effectiveness and economy in the decision making and fulfillment of objectives was evaluated. This thesis seeks to raise awareness among managers of public institutions about the importance of the application of control mechanisms to management, which serve for correct decision making and compliance with institutional objectives that contribute to the benefit of the community. Keywords: audit, management, administrative process, efficiency, effectiveness, economy